A2_4 The contribution of GRBs to cosmological reionization - Evill, Ryland; Johnson, Chris; Rolfe, Samantha; Wilson, Mark (Physics Special Topics, 2009)
High energy gamma ray bursts (GRBs) are considered as an energy source contributing to the cosmological reionization epoch which occurred some 13 billion years ago. The Strömgren radius of a GRB is estimated and compared to the Strömgren radii of other potential sources such as quasars, globular clusters and massive stars. We conclude that GRBs could have an ionizing effect far in excess of these other potential sources given certain assumptions. However, further research is required to determine the overall impact of GRBs on cosmological reionization.